(untitled) (Encuentros, 2017)
This article reviews the academic literature of the concept “News Values” on the first phase research “Effects of the photography of homicide, accidents and injured on the human emotion”. The objective is to research trends, methodology, origin of studies, journals that publish them, among other aspects. The methodology used was content analysis with a sample to 50 articles using inclusion and exclusion criteria. The findings suggest the identification of six emerging trends in academic literature: 1. Typology of news values. 2. Selection of the news. 3. Media coverage. 4. Journalistic routines. 5. Web and 6. Social media. It concludes evidencing a concentration of the research focused in European journals, located in Scopus and null presence studies of Latin America.